(untitled) (Fiep Bulletin - online, 2013)
The research had as approach the education of LIBRAS (Brazilian Language of Signals) as main factor in the psicomotor development in children with auditory deficience of state and municipal public schools. Molinari (2003), affirms that the psicomotricity is the union between emotion, affectivity, body and mind becoming related by means of the action. The act to interpret involves cognitives and linguistic actions, is a process where the interpreter is completely involved in the interaction, ahead of people who present specific communicative intentions (Quadros, 2006). They participate of the present study, 32 pupils, of both the sorts. Evaluations had been made (daily pay and to after) lessons of LIBRAS, using the protocol of Battery "Psicomotora" (BPM), elaborated for Fonseca (1995) The results had been: in the factor A - Tonicidade, the pupils had gotten a significant improvement (p=0,021). In factor B - Balance, the pupils had a satisfactory improvement (p=0,02), a time who found difficulties in this factor. In factor C - Lateralidade, children had not gotten a significant improvement (p=0,083). In factor D - Corporal Notion, the pupils had presented satisfactory corporal evolution (p=0,02). In the factor and - Estruturação space-weather the pupils had gotten significant improvement (p=0,034). In factor F - Global Praxia, the pupils had gotten functional profit in relation its motor independence (p=0,0,0005). In factor G - Fine Praxia, the pupils had gotten a bigger profit (p=0,0,0005). He concludes yourself that the results had pointed 72 lessons of LIBRAS after significant increase of almost all the factors evaluated psicomotores, in 32 pupils folloied for interpreters of the language of signals in public schools. .